The Use of Cyclosporine in Respiratory Diseases - Drew, Jonathan; Maimon, Nimrod; Kalansky, Adie; Refaely, Yael; Alnasasra, Hilmi; Waldman, Maor (Current Respiratory Medicine Reviews, 2013)
Cyclosporine, also known as cyclosporine A (CsA), works primarily as an immunosuppressant by the inhibition of interleukin and immunomediator synthesis. It was first approved for clinical use for the prevention of transplant rejection. The objective of this review is to describe the use of CsA in lung illnesses, emphasize the disadvantages due to the risk of side effects such as immunosupression and nephrotoxicity, and pinpoint where CsA is most useful in today's evolving treatment protocols. CsA is available in both modified and unmodified forms, modification of the drug improves the oral bioavailability. Its administration is limited mainly due to nephrotoxicity and immunosuppression. Patients who receive high doses, particularly transplant patients, are prone to opportunistic infections. Clinically it has several respiratory uses, some of which are still under investigation. One of the main uses is to prevent rejection in lung transplants, which manifests as bronchiolitis obliterans. CsA is used as part of a triple regimen in lung transplant patients, which targets the T-cell role in lung rejection. It is currently under investigation for use via aerosol delivery for prevention of chronic rejection. Other known clinical uses are in inflammatory and infiltrative lung diseases. In cases of asthma it is an option as a steroid sparing treatment, and remission therapy in cases of Idiopathic Pulmonary Fibrosis (IPF) refractory to pulse therapy. In cases of Interstitial Lung Diseases (ILD) CsA was preferred where infiltration was of a predominately cellular type as opposed to fibrotic type. Survival benefit was shown in case reports of Wegener’s granulomatosis, Churg-Strauss syndrome, and arthritis associated interstitial lung disease, especially by achieving steroid sparing effect.
Keywords: cyclosporin